Effect of calculated VOLL and EENS parameters on reserve planning in power system - Tur, Mehmet Rıda; Bayındır, Ramazan; Wadi, Mohammed; Shobole, Abdulfetah; Marhraoui, Saloua; Wadi, Mohammed; Shobole, Abdulfetah Abdela (Institute of Electrical and Electronics Engineers Inc., 2019)
The steady development in the liberalization of the energy sector has made it necessary to consider new policies on energy planning and to consider some socio-economic costs in addition to production costs. These socio-economic parameters are the value of the lost load (VOLL), which is defined as the lost power value or non-electricity cost, and the expected energy not serve (EENS). VOLL is a useful measure for making decisions about the total capacity of power supplies. In terms of consumer payments and suppliers, the marginal price of the system cannot be clearly stated and therefore the lost value cannot be obtained. This value is crucial for countries that are rapidly expanding and structured in terms of electricity supply, and the possibility of supply shortages is predictable. In general, VOLL refers to the monetary value of losses in electricity supply as a result of failures in the production, transmission or distribution sections of electrical power systems. As a result, VOLL can be used as a useful variable to measure one of the dimensions of the energy supply security of a country, region or economic sector. In this study, we obtained an average VOLL and EENS value for the power system with a new approach. In addition, the effects of these values on the planning were examined and their importance was emphasized. © 2019 IEEE.
Fujitsu;Honda;JR-East Group;Nissan Motor Corporation;TMEic
8th International Conference on Renewable Energy Research and Applications, ICRERA 2019 -- 3 November 2019 through 6 November 2019 -- -- 157837
Keywords: Expected energy not served; Power systems economy; Reserve planning; Unit commitment; Value of lost load